Exploration for Deeply Buried Porphyry Copper Deposits in the Southwestern United States (049ab589-2058-40d5-8899-0229df4d4c98) - Theodore H. Eyde (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1975)
The porphyry-copper province of southwestern United States and northern Mexico constitutes the largest copper-producing region in the world. More than 20 deposits discovered since World War II are being exploited or in the process of exploration and development. Because of the remarkable success in discovering new deposits, exploration activity continues at a very high rate and deeper targets are explored each year. Exploration programs for deeply buried porphyry-copper deposits require a reevaluation of the conventional exploration techniques. Though surface induced-polarization techniques have about reached their practical detection limit, aeromagnetics will play an increasing role in the exploration activity as will downhole logging tools. In addition to a valid geological concept, any successful exploration program for porphyry-copper deposits in the southwest must have two other essential ingredients: money and guts. Unfortunately many exploration programs in the southwest are underfunded and doomed to failure. Future exploration will demand more joint venturing in which larger and more expensive exploration programs can be successfully funded by groups of companies or syndicates.